The molecular mechanism of nitric oxide in memory consolidation and its role in the pathogenesis of memory-related disorders - Zainab I. Bahdar (22303855) (2025)
Memory is a dynamic process of encoding, storing, and retrieving information. It includes sensory, short-term, and long-term memory, each with unique characteristics. Nitric oxide (NO) is a biological messenger synthesized on demand by neuronal nitric oxide synthase (nNOS) through a biochemical process initiated by glutamate binding to NMDA receptors, causing membrane depolarization and calcium influx. NO is known to regulate many signaling pathways including those related to memory consolidation. To throw light on the precise molecular mechanism of nitric oxide (NO) in memory consolidation and the possibility of targeting NO pathways as a therapeutic approach to scale down cognitive impairments. We conducted a search of the PubMed MEDLINE database, maintained by the US National Library of Medicine. The search strategy utilized Medical Subject Headings (MeSH) terms, including “nitric oxide and memory,” “nitric oxide synthesis in the brain,” “nitric oxide and Alzheimer’s,” “nitric oxide and Parkinson’s,” and “nitric oxide, neurodegenerative disorders, and psychiatric disorders.” Additionally, relevant keywords such as “nitric oxide,” “memory,” and “cognitive disorders” were employed. We included the most recent preclinical and clinical studies pertinent to the review topic and limited the selection to articles published in English. NO exerts its role in memory consolidation by diffusing between neurons to promote synaptic plasticity, especially long-term potentiation (LTP). It acts as a retrograde messenger, neurotransmitter release modulator, and synaptic protein modifier. The dysregulation of NO balance in the brain can contribute to the pathogenesis of various neurodegenerative diseases, particularly Alzheimer’s, Parkinson’s, and psychiatric disorders. The disturbance in NO signaling is strongly correlated with synaptic signaling dysfunction and oxidative stress. NO plays a fundamental role in memory consolidation, and its dysregulation contributes to cognitive impairment—a hallmark of numerous neurodegenerative and psychiatric disorders. Future research should aim to deepen our understanding of the mechanisms underlying NO’s involvement in memory consolidation and to explore therapeutic strategies targeting the NO pathway to mitigate cognitive decline in affected individuals. Other Information Published in: Neurogenetics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10048-025-00803-0